Comparison Of Erosion-Corrosion Behaviour Of Hot Isostatically Pressed And Welded Stellite Coatings - M. Wong-Kian; L. A. Cornish; A. van Bennekom (The Southern African Institute of Mining and Metallurgy, 1995)
Samples of four different satellite materials were prepared by either hot isostatic pressing (HIP) of the powder or tungsten inert-gas welding of rod onto a 316 L stainless-steel substrate. The samples were subjected to a series of comparative erosion corrosion tests, and generally the Hipped samples experienced between 13 and 24 per cent less loss in mass than the equivalent welded alloys. Resistance to erosion corrosion increased with increasing carbon, chromium, and tungsten contents. Metallographic studies indicated the differences in carbide content between the different satellite materials, and the differences in morphology between the Hipped and welded samples. Finer and more homogeneous microstructures were